Effects of Silica Nanoparticles on Some Indicators of Fertility and Histological Changes in Male Rats - Alaa Mohammad Hasson Al-Husseini (Journal of Global Pharma Technology, 2018)
The current study has been designed to evaluate the effect of silica Oxide nanoparticles (SiO2NPs) exposure on the reproductive performance of male rats. Forty adult Wistar male rats ( aged 60-70 days with body weight130-140 g), were randomly divided into four equal groups , 10 rats per group : control  group were received physiological saline, and three treated groups were administered by gavage at dose (1 mg , 10 mg and 100 mg/kg Body weight) of SiO2NPs suspension  daily for 22 days,  Body weight , some characters of sperms (sperm count, percentage of motility , abnormality , sperms viability ) and histological changes in testis and epididymis were investigated. The results showed insignificant decrease (p ≥ 0.05) in body weight of three treated groups in comparison with control group. Experimental results obtained from SiO2NPs treated  male rats  showed significant decrease (p<0.05) in sperm count , percentage of motility and viability sperms , while a significant  increase (p<0.05) in  percentage of dead and abnormality sperms  compared to control group, histopathological results revealed changes in tissues of testes such as atrophy in some seminiferous tubules with expanded lining . Also noted tubules in both testis and epididymis are empty from sperms with hyperplasia and damage in stereocilia of tubules lining cells of epididymis.Keywords: SiO2NPs, Rats, Reproductive, Sperm, Testis, Epididymis.